2020
DOI: 10.1021/acsami.0c07803
|View full text |Cite
|
Sign up to set email alerts
|

In Operando Detection of the Onset and Mapping of Lithium Plating Regimes during Fast Charging of Lithium-Ion Batteries

Abstract: Existing in operando methods for detection of plated lithium can only detect the presence of plating after the charge is complete and irreversible damage has already occurred. In this work, the characteristic potential minimum on the graphite electrode during high rate lithiation is proposed and assessed as an in operando technique for detecting the onset of lithium plating. While other studies have shown that rapid self-heating of a cell can cause this type of "voltage overshoot", we confirm through temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 58 publications
3
45
0
Order By: Relevance
“…The onset of Li plating has been correlated with the local minimum in the electrode potential during fast charging. [62] Because Li plating can only occur when the electrode potential drops below 0 V versus Li/Li + , a more gradual potential drop during fast charging will delay the onset of Li plating. [9] Thus, the more gradual voltage drop and lack of a local voltage minimum observed in the LBCO electrode are consistent with the suppression of Li plating.…”
Section: Delayed Nucleation Of LI Platingmentioning
confidence: 99%
“…The onset of Li plating has been correlated with the local minimum in the electrode potential during fast charging. [62] Because Li plating can only occur when the electrode potential drops below 0 V versus Li/Li + , a more gradual potential drop during fast charging will delay the onset of Li plating. [9] Thus, the more gradual voltage drop and lack of a local voltage minimum observed in the LBCO electrode are consistent with the suppression of Li plating.…”
Section: Delayed Nucleation Of LI Platingmentioning
confidence: 99%
“…investigated the effects of high C‐rate on the lithium plating on graphite electrode. [ 89 ] Irreversible lithium plating lowered the anode potential, which leads to rapid performance degradation.…”
Section: Optical Microscopy Studies Of Lithium Batteriesmentioning
confidence: 99%
“…Other researchers have explored the effect of temperature on lithium plating and shown that elevated temperature significantly reduces lithium plating. [16,17] Modeling-based articles have shown an increase in anode porosity should also significantly reduce plating. [18] However, our comprehensive approach of experimental measurements and electrochemical/microstructure modeling shows lithium plating is not a strong function of anode porosity.…”
Section: Introductionmentioning
confidence: 99%